Blended learning in teaching higher mathematics to students with disabilities - A. N. Semakin (Открытое образование (Москва), 2020)
A stable trend in modern education is the transition from traditional or face-to-face learning to blended learning by introducing new online tools into the educational process. The complexity of converting traditional academic disciplines into a blended learning format arises from the need to simultaneously develop two interconnected and at the same time qualitatively different components (traditional and online). A correct balancing of the traditional and online components of blended learning allows making the educational process more comfortable and adaptable to the needs of every individual student. The solution of this problem largely depends on specific features of different academic disciplines. In this paper we propose a solution for basic mathematical disciplines taught to students with disabilities at Bauman Moscow State Technical University.The purpose of the study is to find the optimal organization of the process of studying higher mathematics by students with disabilities at Bauman Moscow State Technical University in the framework of blended learning, combining elements of the traditional teaching in the classroom and elements of online learning.Materials and research methods include the analysis of scientific and methodological literature on blended learning, the preparation and implementation of electronic training materials and teaching aids, the analysis of student performance and feedback, as well as the subsequent educational process adjustment based on the data received.The result of the study is the creation of a balanced two-component structure of the educational process in the framework of blended learning. The traditional component includes lectures, seminars and classroom consultations, and the online component consists of electronic training materials and communication tools via the Internet (email and a means of online consultations). Special hardware and software make online consultations similar in effectiveness to traditional classroom consultations. Every student at any place with access to the Internet is able not only to see and hear other participants of the online consultations, but also to see their notes and, in turn, show them his/her own notes made by hand on a regular sheet paper. The introduction of the online component into the educational process allows reducing the high learning rate typical for traditional learning and making it more acceptable for students experiencing certain health problems.Conclusion: the results of the study are used during classes in four mathematical disciplines: mathematical analysis, analytical geometry, linear algebra and integrals with differential equations, which are taught to students with disabilities in the first and second years of study at Bauman Moscow State Technical University.